Governança em compras públicas: um estudo em uma instituição de ensino superior - Melo, Diego Vieira de (2017)
Society has been charging government improvements in the quality of public services and greater responsibility and efficiency in the resource management. The relationship between citizens and public managers is a clear example of an agency relationship, in which the holder of a resource (principal/citizen) signs a contract with another person (agent/public manager), delegating to him the power of decision and management. One of the characteristics of this relationship is the utility maximizing behavior, when the agent tends to make decisions which maximize the benefits of his own. To minimize this problem, public governance arises, which is a set of practices whose function is to allow the principal to monitor and control the agent’s actions. At the international level, public governance has its main references in study 13, prepared in 2001 by the International Federation of Accountants (IFAC); however in Brazil, its guidelines have been guided by Tribunal de Contas da União (TCU). Therefore, the objective of the present research is to identify if, in the severs’ perception, the public governance practices recommended by TCU and the norms proposed in the "study 13 of IFAC" have been applied by the purchasing/acquisitions sector of Universidade Federal de Uberlândia (UFU). So, it is a unique case study, with a qualitative approach, that used as instruments of data collection the questionnaires, interviews and documentary analysis. The results allowed to conclude that UFU implemented few governance practices recommended by TCU regarding the dimensions of leadership, strategy, control, people and processes. It was verified that the most adopted practices refer to those related to dimension plans, information and knowledge. Thus, it is recommended that the institution direct efforts to implement the absent practices and improve those already implemented, respecting the principles of governance, creating a relationship of transparency on behalf of society.